PROVISIONS OF THE DEATH PENALTY IN THE THEORY OF PUNISHMENT FROM THE PERSPECTIVE OF NATIONAL LEGAL OBJECTIVES - Piong Khoyfung; Mulyono Mulyono (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
The death penalty has been implemented in Indonesia since January 1998, with provisions stated in the Penal Code (KUHP) and regulated in Article 10 and Article 100 of Law No. 1 of 2023. The history of the death penalty in Indonesia can be traced back to 1808 when it was introduced as a means to achieve political stability and uphold the development agenda. In line with the evolution of society and law, the government has retained the death penalty in the Penal Code to provide a stronger deterrent effect against legal disturbances. The imposition of the death penalty for certain criminal acts in the Criminal Law is expected to prevent individuals from committing such crimes. In this perspective, the death penalty aims to achieve state stability in accordance with national goals, including the element of justice. The death penalty is regulated by law as an obligation stemming from the Pancasila legal source. Pancasila is the foundation of the Indonesian state and serves as the fundamental norm with the highest position in the hierarchy of legal norms, including criminal law. Therefore, in deciding the death penalty, national legal considerations must be taken into account to ensure that the sanction provides justice, certainty, and benefits for national law and Indonesian society. In the theory of punishment embraced by the Indonesian people, which is a combined theory incorporating absolute and relative elements, the judge's consideration in determining the death penalty becomes sharper in assessing the aggravating factors of the perpetrator in a criminal case. This combined theory recognizes the element of